4D reconstruction of the past - Doulamis, Anastasios D.; Ioannides, Marinos; Doulamis, Nikolaos D.; Hadjiprocopis, Andreas; Fritsch, Dieter; Balet, Olivier; Julien, Martine; Protopapadakis, Eftychios E.; Makantasis, Konstantinos; Weinlinger, Guenther; Johnsons, Paul; Klein, Michael; et al. (My University, 2013)
One of the main characteristics of the Internet era we are living in, is the free and online availability of a huge amount of data. This data is of varied reliability and accuracy and exists in various forms and formats. Often, it is cross-referenced and linked to other data, forming a nexus of text, images, animation and audio enabled by hypertext and, recently, by the Web3.0 standard. Search engines can search text for keywords using algorithms of varied intelligence and with limited success. Searching images is a much more complex and computationally intensive task but some initial steps have already been made in this direction, mainly in face recognition. This paper aims to describe our proposed pipeline for integrating data available on Internet repositories and social media, such as photographs, animation and text to produce 3D models of archaeological monuments as well as enriching multimedia of cultural / archaeological interest with metadata and harvesting the end products to EUROPEANA. Our main goal is to enable historians, architects, archaeologists, urban planners and a liated professionals to reconstruct views of historical monuments from thousands of images oating around the web.
Keywords: 4D Cultural Content Representation; Aug- mentation and Interaction; Visual Content of Cultural Heritage; Visual Search